Neonatal umbilical myiasis - Kotha, Rakesh; Pandala, Paramesh; Singh, Himabindu; Reddy, B. Swetha; Reddy, S. Tejaswi; Rathod, Mahesh; Rhajkumar, E. P. (International Journal of Contemporary Pediatrics, 2019)
Infestation is a state of being invaded or overrun by parasites. Myiasis is an infestation caused by dipterous fly. Even though human myiasis is a rare infestation particularly in newborn period unlike animal myiasis as neonate is just newly introduced to the environment and during this period neonate usually more protected and taken care by us. In rural areas of tropical countries where good hygiene conditions will not be there, authors are still identifying these cases. Risk factors for myiasis usually poor socioeconomic conditions and unhygienic environment. Finding cases of umbilical myiasis usually indicates poor environmental sanitary measures at that particular place. Here authors are presenting a case of neonatal umbilical myiasis caused by Chrysomya megacephala. These flies usually lay their eggs over the wounds or moisture dead necrotic tissues unlike other species of flies where they usually lay eggs over the animal fecus. But some other free-living flies(saprophagous) also cause myiasis due to accidental laying of eggs over dead necrotic tissues due to open defecation. In present case authors identified myiasis as early as third completed day of life, means infestation occurred at the time of delivery as incubation period for hatching eggs to larvae usually 4-8 days. These larvae able to survive inside deep tissue by breathing through a small hole. Even though myiasis usually have good prognosis it will become a focus for secondary infections. If deep-seated causes severe morbidity and even in extreme cases causes death also. Diagnosis is mainly clinical, authors can identify the species by microscopic examination of third stage larvae and finding age of the larvae also useful in identifying time of infestation. Treatments usually direct removal of larvae from the site by manipulation, irrigation, suffocation by ether and surgery if deep-seated. As they usually create nadir for infection by bacteria ruling out secondary infection and treatment is necessary. It is better to take preventive strategies like birthplace cleanliness and environmental sanitation. Tracking the case helpful in finding the places where authors need to improve sanitary measures it is better to give feedback to appropriate administrative officers to prevent home deliveries.